Estimation of the lipophilicity of purine-2, 6-dione-based TRPA1 antagonists and PDE4/7 inhibitors with analgesic activity. (1st October 2021) - Dąbrowska, Monika; Starek, Małgorzata; Chłoń-Rzepa, Grażyna; Zagórska, Agnieszka; Komsta, Łukasz; Jankowska, Agnieszka; Ślusarczyk, Marietta; Pawłowski, Maciej
Graphical abstract: Abstract: Lipophilicity is one of the principal QSAR parameters which influences among others the pharmacodynamics and pharmacokinetic properties of a drug candidates. In this paper, the lipophilicity of 14 amide derivatives of 1, 3-dimethyl-2, 6-dioxopurin-7-yl-alkylcarboxylic acids as multifunctional TRPA1 channel antagonists and phosphodiesterase 4/7 inhibitors with analgesic activity were investigated, using reversed-phase thin-layer chromatography method. It was observed that the retention behavior of the analyzed compounds was dependent on their structural features i.e. an aliphatic linker length, a kind of substituent at 8 position of purine-2, 6-dione scaffold as well as on a substitution in a phenyl group. The experimental parameters (RM0 ) were compared with computationally calculated partition coefficient values by Principal Component Analysis (PCA). To verify the influence of lipophilic parameter of the investigated compounds on their biological activity the Kruskal-Wallis test was performed. The lowest lipophilicity was observed for the compounds with weak PDE4/7 inhibitory potency. The differences between the lipophilicity of potent inhibitors and inactive compounds were statistically significant. It was found that the presence of more lipophilic propoxy- or butoxy- substituents as well as the elongation of the aliphatic chain to propylene one between the purine-2, 6-dione core and amide group were preferable for desired multifunctional activity.